Android-Based Employee Attendance Information System: Sistem Informasi Presensi Karyawan Berbasis Android - Farisy, M. Hilal Al; Fitrani, Fitrani (Indonesian Journal of Innovation Studies, 2022)
The development of information technology in this era is experiencing very rapid development. This is due to the high need for accurate, precise and fast information by humans in doing or completing a job. The influence of the development of information technology has now reached all fields, including the fields of law, agriculture, social, culture, education and business. In this research, an Android-Based Employee Attendance Information System will be built in a case study at PT. Sunjaya Coating Perdana Sidoarjo currently still uses the manual method when taking employee attendance, so using this method is still less efficient. The method used in this study is the waterfall method and software as follows: Visual code as an editor, ReactJS programming language, Javascript framework, Apache web server and MySQL database. This research will produce an android-based employee attendance information system that can make it easier for employees to efficiently attend attendance. And can make it easier for companies to manage employee attendance data.